2014
DOI: 10.1590/0104-1169.3101.2410
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses of newborns with sepsis in a Neonatal Intensive Care Unit

Abstract: Objectives to elaborate the Nursing Diagnoses of newborns with sepsis in a neonatal intensive care unit and characterize the profile of the neonates and their mothers. Method a cross-sectional and quantitative study, with a sample of 41 neonates. A physical examination and consultation of the hospital records were undertaken, using an instrument. The elaboration of the Nursing Diagnoses followed a process of diagnostic inference and was based on the North American Nursing Diagnosis Association 2012-2014. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…One factor influencing the selection of some nursing diagnoses when assessing the defining characteristics and related factors is, according to the authors, the mother's level of knowledge about care for the newborn. In a quantitative cross-sectional study, Brazilian authors Santos et al (2014) identified nursing diagnoses according to NANDA International 2012-2014 and their defining characteristics in 41 newborns with sepsis, who were hospitalized in a neonatal intensive care unit (Rabasová, 2015 (00031). A 95% confidence interval was most significant for the first five of the above nursing diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…One factor influencing the selection of some nursing diagnoses when assessing the defining characteristics and related factors is, according to the authors, the mother's level of knowledge about care for the newborn. In a quantitative cross-sectional study, Brazilian authors Santos et al (2014) identified nursing diagnoses according to NANDA International 2012-2014 and their defining characteristics in 41 newborns with sepsis, who were hospitalized in a neonatal intensive care unit (Rabasová, 2015 (00031). A 95% confidence interval was most significant for the first five of the above nursing diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…After being analyzed, five articles were selected, for being better suited to the purpose of this study and presenting significant relevance for the study. Among the authors of these articles are: Santos et al (15) , Oliveira, Souza and Silva (16) , Neves, Araújo and Lacerda (17) , Urakawa and Kobayashi (18) , and Del'Angelo et al (19) .…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…Neonatal sepsis, or primary infection of the bloodstream (BSI) is a clinical syndrome characterized by a systemic inflammatory response (SIR), with or without evidence of a suspected or confirmed infection. It is one of the more frequent infectious pictures in the neonatal period, and is the one which most raises morbidity and mortality (Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%